DRSO-EGSM: data replication strategy oriented to automatic energy gear-shifting mechanism. (2017) - You, Xindong; Li, Yeli; Zhu, Zhenyang
Recently, more and more attention has been paid on research of cloud storage system. However, with the rapid growth of data volume, the problem of high energy consumption and low efficiency has become the key factor for restricting its development. In order to provide better support for the energy gear-shifting mechanism, we designed an energy-effective data replicating strategy (DRSO-EGSM). Firstly, data is classified into two categories, based on which the number of replicas is determined. And then the replica placement strategy oriented to energy efficiency is designed. Corresponding performance model and energy consumption model are established for data partitioning strategy. Meanwhile, the energy effectiveness of the DSRO-EGSM is evaluated in GridSim simulator. Compared with current existing similar mechanisms TDCS and the default replication strategy of HDFS, substantive results obtained from simulation experiments show that DSRO-EGSM can have more advantages in reducing energy consumption while guaranteeing the system performance.